2013
DOI: 10.1038/onc.2013.150
|View full text |Cite
|
Sign up to set email alerts
|

HBx-mediated miR-21 upregulation represses tumor-suppressor function of PDCD4 in hepatocellular carcinoma

Abstract: The hepatitis B virus (HBV) X protein (HBx) has a key role in the molecular pathogenesis of HBV-related hepatocellular carcinoma (HCC). However, the mechanism of HBx-mediated hepatocarcinogenesis remains to be elucidated. In this study, we aimed to better understand the effects of HBx on gene-expression profiles that participate in hepatocarcinogenesis and the mechanism by which HBx regulates these genes. Differentially expressed genes between L02-HBx and L02-Vector control cells were identified by microarray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 45 publications
2
73
0
Order By: Relevance
“…miRNAs are believed to be an essential regulator in a wide range of human biological processes such as proliferation, apoptosis, cell cycle, and metastasis [28]. miRNAs may function as oncogene-or tumor-suppressive genes depending on the target genes.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are believed to be an essential regulator in a wide range of human biological processes such as proliferation, apoptosis, cell cycle, and metastasis [28]. miRNAs may function as oncogene-or tumor-suppressive genes depending on the target genes.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 (17q23), as an oncogene, is the most frequently in the development of many types of human cancers and in prostate cancer and patient follow-up [50][51][52]. Some studies reported that invasive tumors have over expression of miR-21 by targeting PTEN, TPM1, and PDCD4 genes in prostate cancer specimens [53,54]. The expression levels of miR-21, miR-125b, and miR-141 were highly expressed in prostate cancer as oncogenesis [55,56].…”
Section: Mirna In Prostate Cancermentioning
confidence: 99%
“…Moreover, HBx transgenic mice often de velop liver cancer [24,25] , and HBx protein has been found to accumulate in hepatocytes, affecting the expression of genes associated with signal transduction, cell cycle control, transcription, and immune response [23,26] . Expression of genes on the Xchromosome is regulated epigenetically, including by DNA and histone methyltransferases [27,28] , and by microRNAs [29,30] .…”
Section: Hbv-related Proteins and Their Roles In Hepatocarcinogenesismentioning
confidence: 99%